Muslim preaching in the Middle East and beyond : historical and contemporary case studies (Edinburgh University Press, 2020)
Explores the ways in which Muslims relate various forms of religious oratory to authoritative tradition in 21st-century Islamic practice, while striving to adapt to local contexts and the changing circumstances of politics, media and society.